Issue in ethics. - Fielder, J.H (IEEE Engineering in medicine and biology magazine)
Dead on arrival (subtitled The Politics of Health Care in Twentieth-Century America) is a thoroughly researched and thoroughly depressing story about how the United States came to be the only industrialized country without national health insurance. Heath care is so fundamental to human existence that denying it to those who are in need is rather like denying them food when they are starving. A rich country that is too selfish to allow one out of every seven of its citizens to get decent healthcare is hardly just, compassionate, or admirable. This is particularly ironic when we pride ourselves on our strong sense of individual responsibility and the rewards it brings in competition with others. A fair competition is one in which each person has a reasonable chance to compete, so that reward is based on individual effort and talents. But those who are handicapped by lack of access to healthcare don't have a reasonable chance at obtaining life's satisfactions. For them, the competition is a sham; the game is rigged. There are only a handful of things that make me ashamed to be an American: this is one of them.